Platelet Activation Induced by lnterleukin-6: Evidence for a Mechanism Involving Arachidonic Acid Metabolism - Oleksowicz, Leslie; Mrowlec, Zbignelw; Zuckerman, Dina; Isaacs, Randi; Dutcher, Janice; Puszkin, Elena (Thrombosis and Haemostasis, 1994)
The effect of IL-6 on in vitro platelet function was investigated. Platelet-rich plasma (PRP) incubated with IL-6 showed a dose dependent enhancement of agonist induced maximum aggregation (AIMA) and secretion of thromboxane B2 (TXB2) as measured by RIA, in short term incubations. Dazoxiben (0.2 to 160 (µM) pretreated PRP incubated with IL-6 and aggregated with ionophore A23187, showed a dose dependent inhibition of TXB2 secretion concomitant with a dose dependent abrogation of IL-6’s enhancement of AIMA. A similar abrogation of AIMA was observed when these experiments were repeated using indomethacin. Further, PRP incubated with IL-6 showed a dose dependent increase in TXB2 and BTG secretion as measured by RIA and an increased incorporation of actin binding protein, talin, and myosin into the cytoskeletal core (triton insoluble residue) as shown by SDS-PAGE. The integrin glycoprotein Ilia (GPIIIa) was also observed to be retained into the cytoskeleton by immunoblot. These results suggest that IL-6 activates platelets in vitro and enhances AIMA via a mechanism involving arachidonic acid metabolism.